INTEGRASI ILMU-ILMU ISLAM - Mufid, Fathul (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2013)
The purpose of this article is to analyze how to integrate between science and religion. Islamic theology is based revelation, hadith and ijtihad while science is based on human thinking through research on empirical data. Both Islam and Science have different resources and areas which is separated from each other. The dichotomy mindset is still most Muslims today. There are many Muslims who believe that science and religion stand indifferent position , because science relies empirical data , while religion relying on dogma and also religion are not necessarily based on empirical data , but rather based on “ faith “ or belief . Some Muslim scholars have debated about the Islamization of knowledge such as: Ismail Raji al - Faruqi , Syed Muhammad Naquib Al - Attas , Fazlur Rahman , and Ziauddin Sardar . The idea of “ Islamization of knowledge “ is because of the disparities of achievement between science and religion.